Orphan nuclear transcription factor TR3/Nur77 regulates microvessel permeability by targeting endothelial nitric oxide synthase and destabilizing endothelial junctions - Zhao, Dezheng (National Academy of Sciences, 2011)
Low-level basal vascular permeability (BVP) provides nutrients to normal tissues, and increased vascular permeability is characteristic of inflammation and cancer. We recently reported that VEGF-A, a potent vascular permeabilizing and angiogenic factor, exerts much of its angiogenic activity by up-regulating expression of TR3/Nur77, an orphan nuclear transcription factor, in vascular endothelial cells (EC). To determine whether TR3/Nur77 had a more general role in regulating vascular permeability, we found that histamine, serotonin, and platelet-activating factor, small molecule vascular permeabilizing agents, also increased TR3/Nur77 expression acutely in EC. BVP and the acute vascular hyperpermeability (AVH) induced by these vascular permeabilizing factors were greatly decreased in Nur77(−/−) mice, and both BVP and AVH correlated with Nur77 expression levels in several different mouse strains. BVP and AVH were enhanced in transgenic mice in which Nur77 was selectively overexpressed in vascular EC, whereas both were suppressed in mice overexpressing dominant-negative Nur77. Chronic vascular hyperpermeability (CVH) was induced long before the onset of angiogenesis in a modified, in vivo Matrigel assay that included PT67 cells packaging retroviruses expressing Nur77-sense, whereas inclusion of cells packaging viruses expressing Nur77-antisense prevented VEGF-A–induced CVH. TR3/Nur77 modulated vascular permeability by increasing endothelial nitric-oxide synthase expression and by downregulating several EC junction proteins that maintain vascular homeostasis. Both functions required TR3/Nur77 transcriptional activity. Taking these data together, TR3/Nur77 is up-regulated by several vascular permeabilizing agents and has critical roles in mediating BVP, AVH, and CVH.